2002
DOI: 10.1038/labinvest.3780442
|View full text |Cite
|
Sign up to set email alerts
|

Eotaxin Expression by Epithelial Cells and Plasma Cells in Chronic Asthma

Abstract: SUMMARY:Chemoattractants such as eotaxin are believed to play an important role in the recruitment of eosinophils into the airways in asthma. We investigated expression of eotaxin in the airway wall in a model of chronic human asthma, in which systemically sensitized mice were exposed to low mass concentrations of aerosolized antigen for 6 weeks. In these animals, the number of intraepithelial eosinophils in the airways was significantly increased 3 hours after exposure and declined by 24 hours. In parallel, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…We have previously shown that accumulation of intraepithelial eosinophils is related to upregulation of expression of eotaxin in the airway epithelium in response to inhalational challenge [15]. To investigate whether the mechanism of the reduction in numbers of eosinophils in antagomir-treated mice was related to inhibition of expression of eotaxin, we performed immunostaining on sections of tracheas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that accumulation of intraepithelial eosinophils is related to upregulation of expression of eotaxin in the airway epithelium in response to inhalational challenge [15]. To investigate whether the mechanism of the reduction in numbers of eosinophils in antagomir-treated mice was related to inhibition of expression of eotaxin, we performed immunostaining on sections of tracheas.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoperoxidase staining of formalin-fixed, paraffin-embedded sections was performed following antigen retrieval in 0.01M citrate buffer (pH 6.0), as previously described [15]. Intensity of immunoreactivity was semi-quantitatively scored as grade 0 = no staining, grade 1 = weak staining, grade 2 = moderate staining and grade 3 = strong staining.…”
Section: Methodsmentioning
confidence: 99%
“…OBF.1/BOB.1 is essential for V(D)J recombination by directly enhancing Ig kappa gene transcription, and in OBF.1/BOB.1 Ϫ/Ϫ mice, the production of Ig isotypes is profoundly reduced (43). The increase in OBF.1/BOB.1 expression by ant-miR-126 treatment resulted in high expression of transcripts that code for Ig chains and are likely to be derived from plasma cells that infiltrate the airways wall during allergic airways inflammation (44). Recently, a critical role of OBF.1/ BOB.1 in activation of the transcriptional factor PU.1 and for T H 2 cell function has been shown in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…However, in our study using chronic low-dose challenge, expression of eotaxin by airway epithelium was undiminished in mice treated with anti-CD4 antibody. We have recently demonstrated up-regulation of the induction of eotaxin and other eosinophil chemoattractants in this model as compared with short-term, high-level exposure models (Kumar et al, 2002b), and we speculate that this may account for the lack of effect of administration of anti-CD4 on eosinophil recruitment.…”
Section: Foster Et Almentioning
confidence: 97%
“…We have previously shown that in chronically challenged mice, expression of eotaxin by airway epithelial cells is maximal 3 hours after inhalational exposure (Kumar et al, 2002b). Airway epithelium was strongly immunoreactive for eotaxin both in mice treated with control antibody and in those treated with anti-CD4.…”
Section: Immunohistochemistrymentioning
confidence: 99%